Corporate wrongdoing on film : the 'public be damned' - Dowler, Kenneth; Antonowicz, Daniel H. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Corporate Wrongdoing on Film: The 'Public Be Damned' provides a unique and ground-breaking analysis of corporate wrongdoing depictions, identifying, describing, and categorizing harms perpetrated by corporations. The book provides a history of corporate wrongdoing in film, from the silent film to the present day. Early films are summarized and discussed within the historical, social and political contexts in which they were released. Examining films produced after 1979, the book classifies them by corporate harms to the environment, workers, consumers, and the economy. The book includes a discussion of well over 100 films, from obscure television movies to Hollywood blockbusters. Finally, the book concludes with a narrative analysis exploring the depiction of the protagonists, antagonists, and victims within the corporate wrongdoing film. Detailed and accessible, Corporate Wrongdoing on Film: The 'Public Be Damned' will be of great interest to scholars and students of Criminology and Film and Media Studies"--
An Introduction -- History of Corporate Harm on Film, 1930s to 1970s -- Harm to the Environment -- Harm to Workers -- Harm to Consumers -- Harm to the Economy -- The Social Construction of Corporate Harms.
Keywords: Corporations -- Corrupt practices; Business ethics in motion pictures